PENGAMBILAN KEPUTUSAN PADA WANITA KORBAN PERSELINGKUHAN DI SUMBAWA BESAR - Shofy Nurasyifa Azmi; Ayuning AtmasarI; Yossy Dwi Erliana (Fakultas Psikologi dan Humaniora- Universitas Teknologi Sumbawa, 2021)
Decision-making is the best considered alternative process by individuals covering the steps to go through, but for some people the choice is not easy. Especially for women who are victims of an affair in his household relationships. Decision making requires consideration of some alternatives for the best chosen alternatives. The purpose of this research is to know how to make decisions on women of an affair victim.This research was conducted in the city of Sumbawa Besar with 2 people subject number. The technique of capturing subjects using purposive sampling. The method used is qualitative descriptive. Research data is obtained from interviews, observations and documentation. The results of this study stated that there was a difference in decision making in women who were victims of infidelity. Subject I decided to divorce, while subject II decided to defend his household. As for the factors affecting both subjects in making decisions is a personal factor especially in terms of education and economic circumstances, and social factors, namely the family. Another thing that is not less important in the decision making of both subjects is the child